Relevance of discrete traits in forensic anthropology: From the first cervical vertebra to the pelvic girdle. (August 2015) - Verna, Emeline; Piercecchi-Marti, Marie-Dominique; Chaumoitre, Kathia; Adalian, Pascal
Highlights: The eight discrete traits selected have a frequency inferior to 10%. Supraclavicular foramina were found only in males and only on the left clavicle. Coracoclavicular joints were observed only in males and pubic spines were observed. The majority of individuals with a suprascapular foramen were older than 50 years of age. No association between traits was highlighted. Abstract: In forensic anthropology, identification begins by determining the sex, age, ancestry and stature of the individuals. Asymptomatic variations present on the skeleton, known as discrete traits, can be useful to identify individuals, or at least contribute to complete their biological profile. We decided to focus our work on the upper part of the skeleton, from the first vertebra to the pelvic girdle, and we chose to present 8 discrete traits ( spina bifida occulta, butterfly vertebra, supraclavicular nerve foramen, coracoclavicular joint, os acromiale, suprascapular foramen, manubrium foramen and pubic spine), because they show a frequency lower than 10%. We examined 502 anonymous CT scans from polytraumatized individuals, aged 15 to 65 years, in order to detect the selected discrete traits. Age and sex were known for each subject. Thin sections in the axial, coronal and sagittal planes and 3D volume rendering images were created and examined for the visualization of the selected discrete traits. Supraclavicular foramina were found only in males and only on the left clavicle. Coracoclavicular joints were observed only in males. The majority of individuals with a suprascapular foramen were older than 50 years of age. Pubic spines were observed mostly in females. Other traits did not present significant association with sex, age and laterality. No association between traits was highlighted. Better knowledge of human skeletal variations will help anthropologists come closer to a positive identification, especially if these variations are rare, therefore making them more discriminant.